Direct Observation of the Microscopic Reverse of the Ubiquitous Concerted Metalation Deprotonation Step in C-H Bond Activation Catalysis - Hammarback, L Anders; Aucott, Benjamin J; Bray, Joshua T W; Clark, Ian P; Towrie, Michael; Robinson, Alan; Fairlamb, Ian J S; Lynam, Jason M (Journal of the American Chemical Society, 2021)
The ability of carboxylate groups to promote the direct functionalization of C-H bonds in organic compounds is unquestionably one of the most important discoveries in modern chemical synthesis. Extensive computational studies have indicated that this process proceeds through the deprotonation of a metal-coordinated C-H bond by the basic carboxylate, yet experimental validation of these predicted mechanistic pathways is limited and fraught with difficulty, mainly as rapid proton transfer is frequently obscured in ensemble measures in multistep reactions (i.e., a catalytic cycle consisting of several steps). In this paper, we describe a strategy to experimentally observe the microscopic reverse of the key C-H bond activation step underpinning functionalization processes (viz. M-C bond protonation). This has been achieved by utilizing photochemical activation of the thermally robust precursor [Mn(ppy)(CO) ] (ppy = metalated 2-phenylpyridine) in neat acetic acid. Time-resolved infrared spectroscopy on the picosecond-millisecond time scale allows direct observation of the states involved in the proton transfer from the acetic acid to the cyclometalated ligand, providing direct experimental evidence for the computationally predicted reaction pathways. The power of this approach to probe the mechanistic pathways in transition-metal-catalyzed reactions is demonstrated through experiments performed in toluene solution in the presence of PhC H and HOAc. These allowed for the observation of sequential displacement of the metal-bound solvent by the alkyne, C-C bond formation though insertion in the Mn-C bond, and a slower protonation step by HOAc to generate the product of a Mn(I)-catalyzed C-H bond functionalization reaction.